LDHA-mediated glycolysis in stria vascularis endothelial cells regulates macrophages function through CX3CL1-CX3CR1 pathway in noise-induced oxidative stress - Ying Yi; Min-Yu Wu; Kai-Tian Chen; An-Hai Chen; Lin-Qiu Li; Qin Xiong; Xian-Ren Wang; Wen-Bin Lei; Guan-Xia Xiong; Shu-Bin Fang (Cell Death and Disease)
Abstract According to the World Health Organization, more than 12% of the world’s population suffers from noise-induced hearing loss (NIHL). Oxidative stress-mediated damage to the stria vascularis (SV) is one of the pathogenic mechanisms of NIHL. Recent studies indicate that glycolysis plays a critical role in endothelial cells (ECs)-related diseases. However, the specific role of glycolysis in dysfunction of SV-ECs remain largely unknown. In this study, we investigated the effects of glycolysis on SV-ECs in vitro and on the SV in vivo. Our previous research identified the glycolysis pathway as a potential mechanism underlying the SV-ECs injuries induced by oxidative stress. We further examined the expression levels of glycolytic genes in SV-ECs under H2O2 stimulation and in noise-exposed mice. We found that the gene and protein expression levels of glycolytic-related enzyme LDHA significantly decreased at early phase after oxidative stress injury both in vitro and in vivo, and exhibited anti-inflammatory effects on macrophages (Mφ). Moreover, we analyzed the differential secretomes of SV-ECs with and without inhibition of LDHA using LC-MS/MS technology, identifying CX3CL1 as a candidate mediator for cellular communication between SV-ECs and Mφ. We found that CX3CL1 secretion from SV-ECs was decreased following LDHA inhibition and exhibited anti-inflammatory effects on Mφ via the CX3CR1 pathway. Similarly, the pro-inflammatory effect of LDHA-overexpressing SV-ECs was attenuated following inhibition of CX3CL1. In conclusion, our study revealed that glycolysis-related LDHA was reduced in oxidative stress-induced SV-ECs, and that LDHA inhibition in SV-ECs elicited anti-inflammatory effects on Mφ, at least partially through the CX3CL1-CX3CR1 pathway. These findings suggest that LDHA represent a novel therapeutic strategy for the treatment of NIHL.